Percepção do enfermeiro acerca das mães contraindicadas a amamentar no alojamento conjunto - Rocha, Tatiane Negrão Assis da (2016)
Breastfeeding is arguably considered the world as the ideal way to feed the baby and is characterized as a predictive factor for this health promotion, providing protection against morbidity and mortality. However, in some very limited situations, the Ministry of Health contraindication to breastfeeding. And in these situations it is believed to be essential to think of the mothers who had contraindicated breastfeeding and negative feelings that can come from this experience. Objective: understand the perception of nurses about the mothers who experience conditions that contraindicate breastfeeding and recognize the experience of caring for mothers who had the breastfeeding contraindicated. Methods: A descriptive and exploratory study with a qualitative approach. Attended nineteen nurses who work in rooming in two referral hospitals in Aracaju, SE. Data were analyzed using content analysis and based on the Theory of Symbolic Interaction. Results: Nurses noticed that mothers who have displayed against breastfeeding require more attention and care. They realized even when these mothers understand that not breastfeeding protects their babies have feelings of consciousness, conformity and acceptance, as well as sadness, frustration, fear, anguish, shame, embarrassment, guilt, and escape when they experience the conviviality of rooming with women who can breastfeed, and due to bandaging the breasts. It was found that the participants considered that it is important to protect the privacy of mothers who had contraindicated breastfeeding, as these are allocated in private environments. The bandaging the breasts remained widely used as a measure associated with pharmacological inhibition of lactation, though no longer recommended by the Ministry of Health. It was found that nurses prioritize orientation actions and they see the importance of the host to these mothers. Conclusion: Nurses demonstrated their perception of mothers contraindicated breastfeeding in rooming. The study demonstrated the need for concern with the provision of more skilled nursing care, and sensitively provide care, support and guidance, seeking to understand the uniqueness that each situation requires. In this context, the researcher's perspective was supported by the Theory of Symbolic Interactionism.